Penentuan Tarif Pelayanan Gigi dan Mulut dengan Metode ABC pada Poli Gigi Umum RSGM UNIMUS - Dwi Windu Kinanti Arti; Muhammad Hoesin Dwi Saputra (Universitas Muhammadiyah Semarang, 2021)
Background: The existence of Faculty of Dentistry has contributed to the establishment of the dental and oral hospital. A faculty of dentistry must have a dental and oral hospital as an effort to improve the quality of dentists and general patient care. Activity based costing is an accounting information system that identifies various activities done by an organization and calculates the costs of a product based on the activities required to produce, implement, and distribute it. The objective of the present study was to determine and realize dental and oral service costs using the ABC method at the general dental polyclinic of Unimus dental hospital. Method: This research is a qualitative descriptive case study design with open end method in form of Focus Group Discussion (FGD) with the director and management of Unimus dental hospital. Result: Based on the calculation of the cost for services at the general dental polyclinic of Unimus dental hospital with Activity Based Costing, it can be concluded that the highest cost is Rp. 1,202,809 for the service of Odontectomy M3 Class I A, and the lowest cost is Rp. 106,670 for Anamnesis / consultation without any action. The range is a result of discrepancies in the disposable items used in each of the action or service. Conclusion: The tariff has been concluded through Focus Group Discussion (FGD) with the director and management of Unimus dental hospital with accordance to the policy that 30% is allocated for medical service cost and 30% is apportioned for profit as the management expects.